Why is Anatomy Difficult to Learn? The Implications for Undergraduate Medical Curricula. Issue 6 (2nd April 2021) - Cheung, Chun Chung; Bridges, Susan M.; Tipoe, George L.
Abstract : The impact of the medical curricular reform on anatomy education has been inconclusive. A pervasive perception is that graduates do not possess a sufficient level of anatomical knowledge for safe medical practice; however, the reason is less well‐studied. This qualitative study investigated the perceived challenges in learning anatomy, possible explanations, and ways to overcome these challenges. Unlike previous work, it explored the perceptions of multiple stakeholders in anatomy learning. Semi‐structured interviews were conducted and the transcripts were analyzed by a grounded theory approach. Three main themes emerged from the data: (1) visualization of structures, (2) body of information, and (3) issues with curriculum design. The decreasing time spent in anatomy laboratories forced students to rely on alternative resources to learn anatomy but they lacked the opportunities to apply to human specimens, which impeded the "near" transfer of learning. The lack of clinical integration failed to facilitate the "far" transfer of learning. Learners also struggled to cope with the large amount of surface knowledge, which was pre‐requisite to successful deep and transfer of learning. It was theorized that the perceived decline in anatomical knowledge was derived from this combination of insufficient surface knowledge and impeded "near" transfer resulting in impeded deep and "far" transfer of learning. Moving forward, anatomy learning should still be cadaveric‐based coupled with complementary technological innovations that demonstrate "hidden" structures. A constant review of anatomical disciplinary knowledge with incremental integration of clinical contexts should also be adopted in medical curricula which could promote deep and far transfer of learning.